Participation in the creation of a CD-ROM for French Language Learning in the public secondary education, in collaboration with the Cyprus Ministry of Education and Culture - Georgiadou, Olga (My University, 2026)
Participation in the creation of a CD-ROM for French Language Learning in the public secondary education, in collaboration with the Cyprus Ministry of Education and Culture